1998
DOI: 10.1183/09031936.98.11051141
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of three methods of measuring 99mTc-DTPA lung clearance and their repeatability

Abstract: The lung clearance of technetium-99m diethylenetriamine penta-acetic acid (99mTc-DTPA) is a measure of respiratory epithelial permeability. Many factors may contribute to the wide range of normal values, including the method of correction for background activity. The aim of this study was to compare three methods of analysis, including their repeatability. 99mTc-DTPA lung clearance imaging was performed on eight nonsmokers (age 32+/-2 yrs, forced expiratory volume in one second (FEV1) 102.8+/-3.3% predicted yr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…Lung permeability measurements in this study showed little variation within the subject across three different visits, across the three groups, attesting to the repeatability of this method. In agreement with our findings, Morrison et al demonstrated that lung permeability measurements showed minimal variability in two separate study visits (29).…”
Section: Discussionsupporting
confidence: 93%
“…Lung permeability measurements in this study showed little variation within the subject across three different visits, across the three groups, attesting to the repeatability of this method. In agreement with our findings, Morrison et al demonstrated that lung permeability measurements showed minimal variability in two separate study visits (29).…”
Section: Discussionsupporting
confidence: 93%
“…Counts at peak and 7 min after the peak were taken for calculation. The reason behind the restriction to 7 min after reaching the peak was to minimize the influence of background radioactivity [18]. A least-square fit was carried out for regression analysis.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously demonstrated the reproducibility of the foregoing technique (14). In the case of three chronic smokers, thin layer chromatography (TLC) of residual 99m Tc-DTPA in the nebulizer and of 99m Tc-DTPA in urine demonstrated 0% and Ͻ 1.7% dissociation, respectively, into DTPA and free 99m Tc-pertechnetate (15).…”
Section: M Tc-dtpa Lung Clearancementioning
confidence: 97%